Pengaruh Profitabilitas dan Struktur Modal terhadap Nilai Perusahaan - Santika, Deva; Wijaya, Trisnadi (Universitas Multi Data Palembang, 2024)
The purpose of this research is to examine the effect of profitability and Capital Structure on firm value in manufacturing companies in the consumer goods industry sector on the Indonesia Stock Exchange in 2019-2022, and the approach used is a quantitative approach. This research obtained 37 companies to be studied by applying purposive sampling technique. Then use multiple linear regression analysis for data analysis. The results obtained from this research are profitability and capital structure affect firm value.